Association Between Arterial Hypertension and Periodontal Status in Morbidly Obese Patients Who Are Candidates for Bariatric Surgery - Gerson Aparecido Foratori-Junior; Leonardo Silva Máscoli; Carolina Cordeiro Marchese; Eliel Soares Orenha; Silvia Helena de Carvalho Sales-Peres (Elsevier, 2021)
Objective: This study aimed to compare the systemic and periodontal conditions between morbidly obese patients with and without hypertension who were candidates for bariatric surgery. Methods: The study cohort had 111 morbidly obese patients stratified into two groups: patients with (G1 = 54) and without (G2 = 57) arterial hypertension. The following characteristics were compared between the two groups: (i) education level; (ii) anthropometric parameters [weight, height, body mass index (BMI), waist and hip circumferences and waist-to-hip ratio (WHR)]; (iii) risk of developing cardiovascular diseases (based on patients' sex, age and WHR); (iv) behaviours regarding oral hygiene; and (v) periodontal status. The t-test, Mann-Whitney U-test, chi-square test and logistic regression were applied, with a significance level of 5%. Results: Patients in G1 had a lower level of education (P = 0.002). There were no intergroup differences for weight (P = 0.211), height (P = 0.126), BMI (P = 0.551), waist circumference (P = 0.859) and WHR (P = 0.067); however, patients in G2 had a smaller hip circumference (P = 0.029), and 78% of patients in G1 had a high/very high risk of developing cardiovascular diseases. The prevalence of periodontitis was 72.2% (n = 39) in G1 and 38.6% (n = 22) in G2. On logistic regression analysis, age [adjusted odds ratio (OR) = 1.07; 95% CI = 1.01-1.13; P = 0.008) and the presence of arterial hypertension (OR = 2.77; 95% CI = 1.17-6.56; P = 0.019) were identified as the independent variables associated with periodontitis. Conclusion: Morbid obesity and arterial hypertension are associated with a higher prevalence of cardiovascular diseases. Moreover, morbidly obese patients with hypertension have a higher prevalence of periodontitis and greater severity of periodontal disease than those without hypertension.